Methods of Large Animal Carcass Disposal in Florida - Jan K. Shearer; Max Irsik; Ed Jennings (EDIS, 2008)
VM-171, a 4-page fact sheet by J.K. Shearer, Max Irsik, and Ed Jennings, describes for livestock producers several methods of carcass disposal — burial, composting, tissue digestion, incineration, and rendering. Includes references. Published by the UF College of Veterinary Medicine — Department of Large Animal Clinical Sciences, July 2008.